Local Communities in Tourism Development of Rural Area,A Case Study of Two Local Tourism Initiatives in Wanayasa,Purwakarta - Gunawijaya, Jajang Gunawijay; Pratiwi, Annisa; Nugraha, Irfan (Journal of Indonesian Tourism and Policy Studies, 2016)
This paper describes the challenges in the rural tourism development based on local participation. The rural tourism based on local participation has been identified as ideal model that will uplifting local economy without had significant impacted to their “nature” way of life. However, based on the research on two local groups who are managing the tourism in Wanayasa, we found out that there are challenges in developing the tourism based on local participation. Despite of each groups have differences characteristic in tourism management practice, there are some similarity challenges. Each of groups has facing the external and internal challenges. It shows us that the rural tourism development is the complex process. Furthermore, the integrative model which is including various stakeholders would be an alternative model to optimize the rural tourism development, especially in sustainable tourism